HUBUNGAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI 243 PALEMBANG - Friska Puspita Sari; Sri Wahyuningsih; Mega Prasrihamni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to find out the relationship between student creativity and dance learning outcomes in grade IV of SD Negeri 243 Palembang. The research method used in this study is the quantitative correlation method. The data collection techniques used in this study are questionnaires, dance practice tests and documentation. The results of this study can be seen from data processing using the SPSS Version 26 application and Microsoft Office 2010, it can be concluded that there is a significant relationship between student creativity and dance learning outcomes in grade IV of SD Negeri 243 Palembang because it is based on the results of the calculation of the correlation of person product moment has a significance value of 0.000 < 0.05, therefore student creativity is an important factor in improving dance learning outcomes.